2016
DOI: 10.4103/0019-5049.191669
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile in right lobe living donor hepatectomy: Comparison of lactated Ringer′s solution and normal saline versus acetate based balanced salt solution - a pilot study

Abstract: Background and Aims:Lactate levels predict outcomes after hepatectomy. We compared metabolic effects of lactated versus lactate free solutions in living donor hepatectomy.Methods:Consecutive right lobe donors (n = 53) were alternatively allotted to lactated Ringer's solution and normal saline (Group L-control) or acetated crystalloid (Sterofundin B Braun® Group S -study group) in an observational prospective randomised study. The primary outcome measure was lactate level, and secondary outcomes were base exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…[ 14 ] A study comparing Ringer's lactate with an acetate containing fluid in donor hepatectomy showed no differences in lactate, but an increased metabolic acidosis in the Ringer's lactate group. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] A study comparing Ringer's lactate with an acetate containing fluid in donor hepatectomy showed no differences in lactate, but an increased metabolic acidosis in the Ringer's lactate group. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Acetated Ringer's solution as a new balanced salt solution, compared with slactated Ringer's solution, to maintai n a high levels of bicarbonate and reduce the amount of alkali deficiency, less lead to hyperglycemia (Kumar et al, 2016). And sodium acetate metabolism is seldom dependent on the liver (Kumar et al, 2016). Acetated Ring er's solution compared to lactated Ringer's solution can significantly reduce the body's inflammatory response (Cai et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Higher lactate levels in Ringer acetate group are different from the previous studies conducted by Kumar et al . [ 8 ] in donor hepatectomy and Hadimioglu et al . [ 7 ] in kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al . [ 8 ] concluded that the acetated fluids had higher bicarbonate, lesser base deficit, glucose, and chloride as well as lower lactate than Ringer's lactate with normal saline. Hadimioglu[ 9 ] et al .…”
Section: Discussionmentioning
confidence: 99%